Megakaryocytes and Platelets as the Main Cause for Vascular Events in Chronic Myeloproliferative Disorders - Wehmeier, A.; Schneider, W. (Hämostaseologie, 1996)
Megakaryocytes are part of clonal hematopoiesis in chronic myeloproliferative disorders and are responsible for most of the clinical complications in this disease. About 30-40% of patients with polycythemia vera (PV) and essential thrombocythemia (ET) suffer from thrombotic complications, and microcirculatory disorders are common. Spontaneous bleeding mainly from the gastrointestinal tract is another complication that is especially prevalent in myelofibrosis and advanced stages of chronic myeloid leukemia.In vivo, the bone marrow is hypercellular and the concentration of megakaryocytes increased with characteristic morphological abnormalities. Megakaryocytes are enlarged and ploidy is increased in PV and ET but small mononuclear cells with decreased ploidy are a feature of CML. Despite spontaneous growth in cul-ture, megakaryocytes in chronic MPD are hypersensitive to added interleukin-3, interleukin-6 and GM-CSF.Platelets released from these megakaryocytes show abnormal morphology and ultrastructure, reflected in loss of storage granules and organelles, increased volume distribution and low buoyant density. Uptake, storage and secretion of platelet dense granule constituents is abnormal, and the plasma levels of platelet specific proteins which may also include growth factors for fibroblasts are elevated. At high platelet counts, spontaneous aggregation is observed, whereas agonist-induced aggregation in vitro with adrenaline, ADP and collagen is often defective. Platelet thromboxane generation may be stimulated, and production along the lipoxygenase pathway is decreased. Abnormalities of glycoprotein receptors and decreased fibrinogen binding have been reported but their clinical significance is uncertain. Several observations suggest that not only receptor defects but ineffective intracellular signalling may be responsible for platelet function abnormalities.No single underlying defect has been discovered that could explain this variety of pathological findings. Moreover, a combination of intrinsic megakaryocyte abnormalities and increased susceptibility of platelets to activation makes it difficult to differentiate secondary phenomena from effects of clonal hematopoiesis. How-ever, there are some clinical guidelines for therapy.Most elderly patients will be treated with cytoreductive therapy. Alkylating drugs and 32P have been shown to be leukemogenic, but even hydroxyurea may have a 10% incidence of leukemia induction after long-term therapy. Therapy with platelet-inhibitory drugs is often not sufficient to control thrombosis, and may aggravate a bleeding tendency, so that younger patients with PV and ET are increasingly treated with anagrelide or interferon alpha (A-IFN). Anagrelide is a quinazolin derivative that specifically inhibits megakaryocytopoiesis, while A-IFN may suppress clonal hematopoiesis by an unknown mechanism.
Keywords: Myeloproliferative disorders; megakaryocytes; platelets